Cell-free synthesis of functional phospholipase A1 from Serratia sp. Issue 1 (December 2016) - Lim, Hye; Park, Yu; Jang, Yeon; Choi, Ji; Oh, Joon; Park, Ji; Song, Jae; Kim, Dong-Myung
Abstract Background Phospholipase A1 is an enzyme that hydrolyzes phospholipids at thesn -1 position. It has potential applications across diverse fields including food, pharmaceutical, and biofuel industries. Although there has been increasing interest in the use of phospholipase A1 for degumming of plant oils during biodiesel production, production of recombinant phospholipase A1 has been hampered by low efficiency of gene expression and its toxicity to the host cell. Results While expression of phospholipase A1 inEscherichia coli resulted in extremely low productivity associated with inhibition of transformed cell growth, drastically higher production of functional phospholipase A1 was achieved in a cell-free protein synthesis system where enzyme expression is decoupled from cell physiology. Compared with expression inE. coli, cell-free synthesis resulted in an over 1000-fold higher titer of functional phospholipase A1. Cell-free produced phospholipase A1 was also used for successfully degumming crude plant oil. Conclusions We demonstrate successful production ofSerratia sp. phospholipase A1 in a cell-free protein synthesis system. Including the phospholipase A1 investigated in this study, many industrial enzymes can interfere with the regular physiology of cells, making cellular production of them problematic. With the experimental results presented herewith, we believe that cell-free protein synthesis will provide a viable option for rapid production of important industrial biocatalysts.